COMPARISON ANALYSIS OF JOB STRESS, WORKING CONDITION, AND EMPLOYEE INTENTION TO LEAVE BETWEEN MALE AND FEMALE EMPLOYEES AT PT. BANK SULUT (PERSERO), TBK MANADO - Pokaton, Carla Margaretha (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Nowadays we may find that people get stress easily, considering the demand of good performance of employees is increasing. The objective of this research is to find out if there is any significant difference of job stress, working condition and employee intention to leave between male and female employees at PT. Bank Sulut, Main Branch. The type of research is comparative study. This research uses quantitative method and Independent sample T-test to analyze the data. This research is conducted in Manado with the sample size of 50 respondents, consisting of Â 25 male respondents and 25 female respondents. The result of the study shows that there is significant difference of job stress between male and female employees at PT. Bank Sulut, Main Branch. Another result of the study shows that there is no significant difference of working condition and employee intention to leave between male and female employees. Pressure and bad things that happen on the employees can lead to stress, and when the situation get worse, there will be a probability that an employee intend to leave or quit the job. As the suggestion to prevent job stress and employee intention to leave, they may rearrange their workspace, because that would bring positive energy to the work environment and make it a good working condition. Keywords: employee performance, job stress, working condition, leave intention.